Association of low-density lipoprotein receptor polymorphisms and outcome of hepatitis C infection. - Hennig, B; Hellier, S; Frodsham, A; Zhang, L; Klenerman, P; Knapp, S; Wright, M; Thomas, H; Thursz, M; Hill, A (2002)
The low-density lipoprotein receptor (LDLR) has been proposed to promote hepatitis C virus endocytosis and the cell membrane protein CD81 may also promote HCV host cell entry. The CD81 gene was sequenced to screen for novel polymorphisms, but no SNPs were identified. Polymorphisms within the LDLR gene are associated with the pathogenesis of familial hypercholesterolemia, atherosclerosis and obesity. We therefore studied genetic variation within the LDLR gene and clinical features of hepatitis C infection. An amino acid change in exon 8 was associated with severity of fibrosis; a SNP in exon 10 correlated with viral clearance and overall inflammation, and a SNP in the 3'UTR appeared to influence treatment response. There were no other significant associations between any of the SNPs studied and the clinical measures of hepatitis C infection. We furthermore report on linkage disequilibrium within the gene and haplotype frequencies in our population. Our findings support a possible role for the LDLR in the modulation of disease progression by affecting immune responses, rather than functioning as receptor for HCV.